2014
DOI: 10.1007/s11934-014-0408-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Urolithiasis in Spinal Cord Injury Patients

Abstract: Urolithiasis is a common condition in patients with spinal cord injury (SCI). Surgical management of stones in this population is more challenging and associated with lower clearance rates than the general population. The rate of complications - specifically infectious complications - is also high due to the chronic bacterial colonization. Shock wave lithotripsy (SWL) has a low clearance rate of 44-73 %. Percutaneous nephrolithotripsy is indicated for larger nephrolithiasis, but multiple procedures may be requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…We have also previously shown that indwelling catheters are associated with an increased risk of UTIs and hospitalization for UTIs, in this same cohort 22 . This may be associated with the fact that infections, particularly with Proteus infections, are linked to the formation of stones, like struvite (magnesium ammonium phosphate), one of the most common stones in this population 23 . Interestingly, we found that people with a history of kidney or bladder stones did not have a significantly higher rate of patient‐reported UTIs but did have an increased rate of hospitalizations due to UTI in the year before enrollment.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…We have also previously shown that indwelling catheters are associated with an increased risk of UTIs and hospitalization for UTIs, in this same cohort 22 . This may be associated with the fact that infections, particularly with Proteus infections, are linked to the formation of stones, like struvite (magnesium ammonium phosphate), one of the most common stones in this population 23 . Interestingly, we found that people with a history of kidney or bladder stones did not have a significantly higher rate of patient‐reported UTIs but did have an increased rate of hospitalizations due to UTI in the year before enrollment.…”
Section: Discussionsupporting
confidence: 51%
“…22 This may be associated with the fact that infections, particularly with Proteus infections, are linked to the formation of stones, like struvite (magnesium ammonium phosphate), one of the most common stones in this population. 23 Interestingly, we found that people with a history of kidney or bladder stones did not have a significantly higher rate of patient-reported UTIs but did have an increased rate of hospitalizations due to UTI in the year before enrollment. The reasons for this discrepancy are unclear but may be related to the fact that recall for hospitalizations may be more accurate than UTIs.…”
Section: Discussionmentioning
confidence: 65%
“…One of the main reasons for avoiding surgical treatment for patients with poor PS is the risk of perioperative complications, especially infectious disease. A review of the current literature on the management of urolithiasis in patients with spinal cord injury showed that the overall complication rate in patients with spinal cord injury is higher than in the general population, and the majority of these are infectious in nature are due to the associated medical comorbidities and chronic bacteriuria [ 5 ]. In our study, postoperative pyelonephritis was observed in 16.7% (1/6 cases), 15.4% (6/39 cases) and 16.7% (1/6 cases) of the patients who underwent SWL, URS and PCNL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…SCI patients pose a particular challenge because of their multiple comorbidities, skeletal deformities, previous surgeries, urinary diversions and chronic bacteruria. 5 Open cystolithotomy was historically the procedure of choice, offering excellent stone clearance but with high complication rates and associated morbidity. Particularly, large stones may still require an open procedure; however, the majority of bladder stones in SCI patients are now treated as in the general population: transurethrally with stone punch, electrohydraulic lithotripsy (EHL) or holmium YAG laser, percutaneously, or with extracorporeal shock wave lithotripsy (ESWL).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, large stones may still require an open procedure; however, the majority of bladder stones in SCI patients are now treated as in the general population: transurethrally with stone punch, electrohydraulic lithotripsy (EHL) or holmium YAG laser, percutaneously, or with extracorporeal shock wave lithotripsy (ESWL). The overall complication rate following bladder stone removal in SCI patients is thought to be higher than in the general population; 5 however, there is very limited documentation of the outcomes associated with any of these techniques either in the general population or in SCI patients.…”
Section: Introductionmentioning
confidence: 99%